GAME PENGENALAN HURUF HIJAIYAH BERBASIS FLASH - , YUDHI NURPRATOMO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The development of educational programming that is increasingly prevalent makes the game developers are racing to create educational games that are beneficial, especially for children. However, most educational games are created in the form of general learning, while for games that have educational value is still not Islamic. Therefore, the authors make a game of hijaiyah learning to balance the needs of Islamic education, especially for children This game is adventure genre, where players will be directed to pass through a trap to take hijaiyah. Then, when user took hijaiyah it will instantly sound pronunciation (lafadz) of that. Thus, indirectly this game will provide an introduction hijaiyah to user. More often users are expected to play this gamethe user will get know the characters of hijaiyah so this game could be an effective tool in basic Islamic teaching.